One health for better world and better public health - CHIKHLADZE, Nino (One Health & Risk Management, 2022)
The Journal ,,One Health&Risk Management’’ funded in 2019 by Moldavian Biosafety and Biosecurity Association disseminates important and valuable results of scientific researches from different disciplines under the umbrella ,,One Health’’ which promotes a better world and better public health.